Temporomandibular Joint and Airway Disorders A Translational Perspective (Springer International Publishing, 2018)
This book on the local and systemic manifestations and correlates of temporomandibular joint disorders (TMDs) encompasses the two intertwined facets of translational science - translational research and translational effectiveness - as they relate specifically to TMDs. The first part of the book, on recent translational research, focuses on topics such as the neuroanatomy and neurophysiology of the trigeminal nerve and trigeminal network system, the manifestations of neuroinflammation in TMDs, and the molecular mechanisms underlying TMDs. The second part discusses the clinical effectiveness of treatment approaches from the perspective of evidence-based dentistry, with careful attention to the critical relationships between dental malocclusions, the signs and symptoms of TMDs, and airway/breathing disorders. Interventions to correct for malocclusal conditions that lead to TMDs are examined, with explanation of the ways in which they can ameliorate a variety of local and systemic symptoms. This will be an excellent reference book for established practitioners, residents, interns, and students as well as a powerful cutting-edge document for researchers in the field. .